THU0219 The Infliximab Dose Increase is Not Correlated with Clinical Improvement in RA Patients. (23rd January 2014) - López-Casla, M. T.; Pascual-Salcedo, D.; Plasencia, C.; Alcozer, P.; García-Carazo, S.; Bonilla, G.; Villalba, A.; Peiteado, D.; Arribas, F.; Martín-Mola, E.; Balsa, A.
Abstract : Background: The anti-TNF therapy is an effective treatment in RA patients, however a considerable percentage of patients develop clinical inefficacy (primary or secondary); part of which can be explained by the development of antibodies to infliximab (ATI). In some patients, a dose increase is often used to achieve a clinical improvement, mainly in patients with secondary inefficacy. However, there is no evidence that demonstrates if dose escalation is a good therapeutic option. Objectives: To assess whether increasing the infliximab (Ifx) dose is an effective therapeutic option in RA patients who develop clinical inefficacy. Methods: The present study included 36 RA patients treated since 2000 with Ifx at La Paz University Hospital, in whom a Ifx dose increase was implemented due to inefficacy [23/36 (64%) primary non-responders and 13/36 (36%) secondary non-responders]. All patients started to receive Ifx at 3 mg/kg i.v. at standard schedule. A therapeutic increase was defined as: Ifx dose higher than 3 mg/kg i.v. (until maximum of 5 mg/kg) or interval time between infusion 6-7 weeks. The clinical activity was measured by the Disease Activity Score 28 (DAS28) at baseline, before starting the dose escalation, at 6 months and at 1 year after the dose increase. The drug and ATI levels were measured by a capture and bridging ELISA, respectively. Statistical analysis was made using SPSS system 11.0. Results: Thirty one out of 36 patients (86.1%) were female, with a mean age of 58±13.6 years. The disease duration was 19.2±10.5 years and the time under Ifx therapy was 6.6±3.8 years. Most patients received concomittant therapy with DMARDs [15 (41.7%) methotrexate, 22 (41.7%) other DMARDs and 8 (22.2%) in monotherapy] and 13 (38.2%) received prednisone. All patients were active (DAS28) at baseline and before starting the dose increase (5.4±1.0 at baseline and 4.2±1.2 just before dose escalation). ATI were detected in 13/34 (38.2%) patients at the moment of decision to increase (in 2 patients ATI were already present in the first available sample) and only 2 (5.5%) patients became negative after dose increase. The Ifx increment did not produce significant improvement in clinical activity (DAS28) in RA patients, independently on ATI status [ATI-negative: 4.25±1.4 at pre-increase vs 3.9 ±1.0 at 6 months after increase (p=0.311) and 4.04±1.1 vs 4.03 ±1.3 at 1 year after increase (p=0.970); ATI-positive: 4.09±0.9 at pre-increase vs 4.1±1.3 at 6 months after increase (p=0.945) 3.7 ±0.7 vs 3.0±0.8 at 1 year after increase (p=0.110)]. A total of 26 (76.5%) patients discontinued the Ifx therapy, not identifying differences between ATI-positive patients (15/21, 71.4%) and ATI-negative patients (11/13, 84.6%), p=0.378. Conclusions: Infliximab dose escalation does not seem to be an effective therapeutic option in RA patients who develop primary and secondary inefficacy. Further studies are necessary to confirm these results. Disclosure of Interest: None Declared